The arts and crafts of Syria and Egypt from the Ayyubids to World War I - Milwright, Marcus. (Piscataway, NJ)
xviii, 361 sayfa
Keywords: “This book focuses on the production, sale, and consumption of portable arts in regions covered today by the modern polities of Egypt, Syria, Jordan, Lebanon, and the Palestine Authority. The reprinted chapters in this volume have been revised and updated. They offer interdisciplinary approaches to the material culture of the region from the twelfth to the early twentieth centuries, combining evidence from primary written sources, archaeology, and objects in museums and private collections. Topics include the production and distribution of pottery, importation of glazed wares into the Middle East, shadow puppetry, economic activity associated with the Syrian hajj, the manufacturing practices of the crafts operating in Damascus during the last decades of Ottoman rule, and the decoration of artillery shell cases during and after World War I. Also included are an introduction containing a critical evaluation of the main sources of information, a cumulative bibliography, and a previously unpublished study of leatherworking in the late Ottoman period“ - -Yayıncı.